Substorm Induced Nighttime Plasma Flow Pulsations Observed by ROCSAT‐1 at Topside Ionosphere - S.‐Y. Su; Y.‐Y. Sun; C.‐K. Chao; L.‐C. Tsai; C. H. Liu (Space Weather)
Abstract The Republic of China Satellite‐1 orbiting at 600 km topside ionosphere has observed the topside ionospheric plasma flow pulsations induced by the substorm onsets. These pulsation events indicated that the plasma flow pulsations mainly oscillate in the two mutually perpendicular directions with respect to the geomagnetic field lines. The field‐aligned flow as well as the ion density indicates almost no variation. This implies that the pulsation events are of Alfven wave in nature. The Hilbert‐Huang transform analysis is applied to study the dominant wave frequencies and the polarization in the two perpendicular components of plasma flows (i.e., the perturbed electric/magnetic fields). The hodograms of the polarization in the Pi1 frequency is shown to be linearly polarized, while the left‐handed polarization is seen in the Pi2 frequencies that are in harmonic relationship. These plasma flow pulsations in the nighttime topside ionosphere are caused by the field‐line‐resonance magnetic field pulsations converted from the inward propagated compressional disturbance across the nighttime magnetosphere/plasmasphere which is originated at the near‐Earth magnetotail at the substorm onset.